Building Global Leaders through Field Research and Extension Experiences in Belize - Tom Gill; Adam S Willcox (Journal of International Agricultural and Extension Education, 2022)
One of the most complex agricultural and natural resources challenges of our time is reconciling sustainable global food security and biodiversity conservation. Providing undergraduate students effective, learning experiences to develop technical and cultural competency prepares them to address this challenge and become global leaders in their disciplines. A three-year experiential research and extension project brought together 14 students and 10 faculty mentors to investigate smallholder farmers practicing conservation-compatible adjacent to the Vaca Forest Reserve in Belize. We used an agroecological approach to foster systems-level thinking and develop transdisciplinary skills of undergraduate students. Students completed applied individual research projects that explored the challenge of food security and biodiversity conservation in the tropics, and worked collaboratively with local stakeholders, design and implement extension projects based on research results. Student and faculty teams assessed cropping and soil management practices; social and economic systems; and wildlife, forestry, and ecosystem services. We assessed student learning outcomes with a tool commonly used for evaluating undergraduate research. Students reported learning gains in attitudes and behaviors toward research, mindset towards research, ability to think and work like a scientist, and research skills. Students also reported positive working relationships with mentors and peers, and a high level of publication and presentation outputs. Students reported that their Belize experience helped develop their agroecological and cross-cultural knowledge and skills, and prepared them for their next career steps. We conclude with recommendations for higher education institutions wishing to develop meaningful global undergraduate research experiences that can build the next generation of leaders.
Keywords: workforce development; cultural competency; study abroad; tropical agriculture; biodiversity conservation